MUSEQuBES: The Column Density, Covering Fraction, and Mass of O vi-bearing Gas in and Around Low-redshift Galaxies - Sayak Dutta; Sowgat Muzahid; Joop Schaye; Nicolas F. Bouché; Sebastiano Cantalupo; Hsiao-Wen Chen; Sean Johnson (The Astrophysical Journal)
We present a study of O vi -bearing gas around 247 low-mass (median ${log}_{10}(M_{\star }/M_{\odot })$ = 8.7) galaxies at low redshifts (0.1 < z < 0.7) using background quasars as part of the MUSE Quasar-fields Blind Emitters Survey (MUSEQuBES). We find that the average O vi column density, ${{\rm{log}}}_{10}\left\langle N({\rm{O}}\,{\rm\small{VI}})/{{\rm{cm}}}^{-2}\right\rangle =14.1{4}_{-0.10}^{+0.09}$ , measured within the virial radius for our sample, is significantly lower than for L _* galaxies. Combining 253 star-forming galaxies (mostly more massive) from the literature with 176 star-forming galaxies from MUSEQuBES, we find that both $\left\langle N({\rm{O}}\,{\rm\small{VI}})\right\rangle $ and the average covering fraction peak at ${log}_{10}(M_{\star }/M_{\odot })$ ≈ 9.5. The virial temperature corresponding to this stellar mass is ideal for O vi production via collisional ionization. However, we argue that photoionization and/or nonequilibrium processes are necessary to produce the O vi associated with low-mass, dwarf galaxies ( ${log}_{10}(M_{\star }/M_{\odot })$ < 9). The average O vi mass within the virial radius of dwarf galaxies is measured to be $1{0}^{5.{2}_{-0.1}^{+0.1}}$ M _⊙ . The characteristic normalized impact parameter ( D / R _vir ) at which the O vi covering fraction drops to half of its peak value is largest (≈1.1) for galaxies with stellar mass ${log}_{10}(M_{\star }/M_{\odot })$ ≈ 9.5. We report the presence of a highly ionized metal floor with ${log}_{10}N({\rm{O}}\,{\rm\small{VI}})/{{\rm{cm}}}^{-2}=13.2$ outside the virial radius of dwarf galaxies inferred from median spectral stacking.